2020
DOI: 10.1101/2020.06.25.20140277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic and multi-tissue proteomic integration for understanding the biology of disease and other complex traits

Abstract: Expression quantitative trait loci (eQTL) mapping has successfully resolved some genome-wide association study (GWAS) loci for complex traits. However, there is a need for implementing additional "omic" approaches to untangle additional loci and provide a biological context for GWAS signals. We generated a detailed landscape of the genomic architecture of protein levels in multiple neurologically relevant tissues (brain, cerebrospinal fluid (CSF) and plasma), by profiling thousands of proteins in a large and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…Indeed, we have recently shown that SMOC1 is strongly elevated in AD cerebrospinal fluid (CSF) 26,40,47 . Consistent with our mod-QTL findings, levels of SMOC1 in CSF were recently identified to be influenced by a pQTL associated with the APOE4 genotype 48 .…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, we have recently shown that SMOC1 is strongly elevated in AD cerebrospinal fluid (CSF) 26,40,47 . Consistent with our mod-QTL findings, levels of SMOC1 in CSF were recently identified to be influenced by a pQTL associated with the APOE4 genotype 48 .…”
Section: Discussionsupporting
confidence: 91%
“…In light of recent investigations reporting that the majority of eQTLs do not necessarily influence protein levels (He et al, 2020;Yang et al, 2020) we used MR to identify key eProteins, and eMetabolites, that may influence human lifespan. In order to discover the role of these genetically regulated traits in human homeostasis while at the same time determining whether they could be effectively and safely targeted to promote healthy aging and human longevity, we report MR findings across the human disease-related phenome.…”
Section: Mendelian Randomization (Mr) Is a Burgeoning Field Of Researchmentioning
confidence: 99%
“…The levels of α-Syn were measured in CSF, plasma, and brain (parietal cortex) using an aptamer-based approach (SOMAScan platform) [70]. After stringent quality control, CSF (n = 835), plasma (n = 529), and brain (n = 380) samples were included in the downstream analyses (Additional file 2: Table S2).…”
Section: Multi-tissue Analysismentioning
confidence: 99%